Diagnosing Viral and Atypical Pathogens in the Setting of Community-Acquired Pneumonia - Waterer, Grant W. (Clin Chest Med, 2017)
The ‘atypical’ pathogens causing pneumonia have long been problematic for physicians because we have had to rely on serologic tests to make a diagnosis. The introduction of polymerase chain reaction techniques revolutionized the diagnosis of respiratory infections and now a new wave of technologies promising faster, cheaper, and more comprehensive testing are becoming available. This review focuses principally on the diagnosis of Legionella, Mycoplasma, and influenza infections, but also covers recent publications on the cutting edge of diagnostic tools likely to transform the field of infectious diseases over the coming decade.